Prioritizing research needs: insights from a healthcare organization in Iran - Mohammadkarim Bahadori 1*, Ehsan Teimourzadeh 1, Ali Farzaneh 1, Mostafa Nejati 2 (Archives of Global Professionals, 2011)
Objectives: The goal of this study was to identify the priorityof research needs in a healthcare organization in Iran, based onidentification of the problems faced by patients, as the mainrecipients of healthcare services.Method: A cross -sectional descriptive study was planned toachieve the objectives of study. The service recipients sampleconsisted of 400 patients. Given the necessity to gain in-depthinsights of the subject matter, a qualitative research design waschosen. A number of 50 interviews were conducted withindividuals from among 400 patients. The data was analyzedusing ATLAS.ti softwarePrioritizing of the topics was doneusing Analytical Hierarchy Process (AHP) method and theExpert Choice software.Results: Based on the issues extracted from the interviews anddiscourses, 13 research topics were proposed by experts.Among these, the topics "designing the model of premium andcomplementary franchise payment, proportional to theincome, access and enjoyment", "designing the dental servicespackage with specific premium in three basic, complementaryand optional levels" and "Presenting the model of diseaseprevention in healthcare organizations" acquired the highestpriority ranked 1 to 3 and earning the scores of 0.63, 0.61 and0.41, respectively.Conclusion: Because resources are limited and needs areunlimited, in order to avoid wasting research resources inhealthcare organizations, allocating the resources must bebased on the extracted priorities; and this is vital to fulfill theorganizational objectives.